An Analytical Study of the Intellectual Output Published in the Basra Arts Journal (2013-2022) Stylistic Study - Weshah , Assist. Lect. Khadija (Basra studies journal, 2024)
This research aims to quantify the intellectual output published in the Basra Arts Journal from 2013 to 2022 and to analyze author productivity as well as the topics covered by the journal. A quantitative methodology was utilized. The findings indicate that 626 papers were published in the journal during this period, comprising 535 articles in Arabic and 91 articles in English. The Arabic language was the most prominent subject, with 209 published papers, according to the topical distribution of the research. The study also recommends continuing efforts to publish a second cumulative index for the journal, following the release of the first index, which covered issues 1-82 for the period 1968-2018.